Tracking cruise passengers' consumption: An analysis of the relationships between onshore mobility and expenditure - Caterina Sciortino; Mauro Ferrante; Stefano De Cantis; Szilvia Gyimóthy (Annals of Tourism Research Empirical Insights, 2022)
This paper analyzes the relationships between the spatial behaviour and destination expenditures of cruise tourists by integrating customer surveys and GPS tracking technology. Based on data collated in 2018 and 2019 in Copenhagen, cruise passenger expenditure was modelled via logistic regression, using socio-demographic characteristics and mobility-related variables. In order to map the spatial behaviour and the key characteristics of the itinerary followed, tracking data were synthesized into meaningful mobility variables. An analysis of stops was performed to identify locations with the potential highest expenditure density. The results indicated that spatial movement and, in particular, stop activities are relevant in explaining expenditure behaviour. The implications of the proposed methodology are discussed with regards to further research, and destination management.
Keywords: 330; GPS-tracking; Cruise tourism; Intra-destination mobility; Tourist expenditure; Stop analysis; Mobility